Gut microbial diversity moderates polygenic risk of schizophrenia - Zhang, Liyuan; Yuan, Xiuxia; Li, Xue; Zhang, Xiaoyun; Mao, Yiqiao; Hu, Shaohua; Andreassen, Ole A.; Wang, Yunpeng; Song, Xueqin (Frontiers in Psychiatry, 2024)
Background: Schizophrenia (SCZ) is a heritable disorder with a polygenic architecture, and gut microbiota seems to be involved in development and outcome. Here we investigate the interplay between genetic risk and gut microbial markers. Methods: We included 159 first-episode, drug-naï ve SCZ patients and 86 healthy controls. Microbial compositions of feces were characterized by the 16S rRNA sequencing platform and five microbial -diversity indices were estimated (Shannon, Simpson, Chao1, Abundance-based coverage estimate (ACE) and phylogenetic diversity-based estimates (PD)). Polygenic risk scores (PRS) for SCZ were constructed using data from large-scale genome wide association studies. Effects of microbial -diversity, microbial abundance and PRS on SCZ were evaluated by generalized linear models. Results: We confirmed that PRS were associated with SCZ (OR=2.08, p=1.22x10 -5 ), and that the Shannon (OR=0.29, p=1.15x10 -8 ) and Simpson (OR=0.29, p=1.25x10 -8 ) indices were inversely associated with SCZ risk. We found significant interactions (p<0.05) between PRS and -diversity indices (Shannon, Simpson and PD) with larger PRS effects in those having higher diversity than lower. Moreover, the PRS effects were larger in individuals who have a high abundance in the genera Romboutsia, Streptococcus and Anaerostipes than those who have low abundance (p <0.05). All the three genera showed protective effects on SCZ. Conclusion: The current findings suggest an interplay between gut microbiota and polygenic risk of SCZ that warrants replication in independent samples. Experimental studies are needed to determine the underpinning mechanisms.